China and the United States: It's a Cold War, but don't panic. (4th March 2022) - Daly, Robert
ABSTRACT: In November 2019, Henry Kissinger warned that the United States and China were in "the foothills of a Cold War" that could end in a conflict worse than World War I. Two years, one pandemic, a change of American administrations, and a brutal war in Ukraine later, the relationship is above of the foothills and nearing the summit. Cold War framing now seems inevitable. It has, at least, the virtue of focusing the world's attention.